Hydration and urinary pseudoephedrine levels after a simulated team game - Jolley, D.; Dawson, B.; Maloney, S. K.; White, J.; Goodman, C.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
This study investigated the influence of dehydration on urinary levels of pseudoephedrine (PSE) after prolonged repeated effort activity. Fourteen athletes performed a simulated team game circuit (STGC) outdoors over 120 min under three different hydration protocols: hydrated (HYD), dehydrated (DHY) and dehydrated + postexercise fluid bolus (BOL). In all trials, a 60 mg dose of PSE was administered 30 min before trial and at half time of the STGC. Urinary PSE levels were measured before drug administration and at 90 min postexercise. In addition, body mass (BM) changes and urinary specific gravity (USG), osmolality (OSM), creatinine (Cr), and pH values were recorded. No differences in PSE levels were found 90 min postexercise between conditions (HYD: 208.5 ± 116.5; DHY: 238.9 ± 93.5; BOL: 195.6 ± 107.3 µg·ml-1), although large variations were seen within and between participants across conditions (range: 33-475 µg·ml-1: ICC r = .03-0.16, p > .05). There were no differences between conditions in USG, OSM, pH or PSE/Cr ratio. In conclusion, hydration status did not influence urinary PSE levels after prolonged repeated effort activity, with ~70% of samples greater than the WADA limit (>150 µg.ml-1), and ~30% under. Due to the unpredictability of urinary PSE values, athletes should avoid taking any medications containing PSE during competition.